2016
DOI: 10.21548/32-2-1390
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Identification of Lactic Acid Bacteria Occurring in Must and Wine

Abstract: A specifically amplified polymorphic DNA-polymerase chain reaction (SAPD-PCR), a molecular fingerprinting method based on the amplification of specific gene sequences, was applied in order to allow a rapid identification of lactic acid bacteria (LAB) occurring in must and wine. The applicability of this method was confirmed with isolated strains from different wine samples from the German wine growing region Palatinate. In addition, the formation of biogenic amines by the isolated strains was studied. More tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 38 publications
1
19
0
Order By: Relevance
“…Sebastian et al . () observed that all Lact. brevis isolates (57) were able to form BAs, and four species ( Lact.…”
Section: Bas‐producing Micro‐organismsmentioning
confidence: 95%
See 1 more Smart Citation
“…Sebastian et al . () observed that all Lact. brevis isolates (57) were able to form BAs, and four species ( Lact.…”
Section: Bas‐producing Micro‐organismsmentioning
confidence: 95%
“…cheese, milk, beer, wine). The formation of these low molecular nitrogen compounds is mainly through four enzymatic reactions: (i) decarboxylation, (ii) transamination, (iii) reductive amination, and (iv) degradation of certain precursor amino compounds (Sebastian et al ., ). According to Onal et al .…”
Section: Introductionmentioning
confidence: 97%
“…They originate from the grape berries or are formed during fermentation by activities of decarboxylase-positive microorganisms [98][99][100][101][102]. Although more common in foods such as cheese, BA have received much attention in wine, as ethanol can enhance the negative effects on human health by inhibiting the enzymes responsible for the detoxification of these compounds [101].…”
Section: Phenoloxidasesmentioning
confidence: 99%
“…Reasonable explanations are structural modifications of the peptidoglycan, like N-deacetylation and O-acetylation of the glycan chains or amidation of free carboxyl groups of amino acids in the peptide chains [113]. As a possible alternative to hen's egg white lysozyme, exoenzymes (protease and muramidase) from Streptomyces species showed a broad bacteriolytic spectrum under winemaking conditions [98,113].…”
Section: Lysozymementioning
confidence: 99%
“…hilgardii are examples of producers of biogenic amines (Landete et al, 2005;Mangani et al, 2005;Sebastian et al, 2011;Petri et al, 2013). The most important biogenic amine is histamine, which is produced by decarboxylation of histidine.…”
Section: Introductionmentioning
confidence: 99%